A new species and two new records of symbiotic infaunal alpheid shrimps from the genera Leptalpheus Williams, 1965 and Fenneralpheus Felder & Manning, 1986 (Decapoda: Caridea) from Venezuela - Caripe, Jonathan Vera; Pereda, Luisana; Anker, Arthur (Zootaxa, 2021)
Leptalpheus lirai sp. nov., a new species of symbiotically living, infaunal alpheid shrimp, is described based on a single specimen from the Gulf of Santa Fe, Sucre, Venezuela. The new species belongs to an informal group of nine species within the genus Leptalpheus Williams, 1965, which is characterised by the presence of well-developed adhesive disks on the major chela. In addition, Leptalpheus axianassae Dworschak & Coelho, 1999 and Fenneralpheus chacei Felder & Manning, 1986 are recorded for the first time from Venezuela (Anzoátegui and Sucre, respectively), the latter also representing the first record of the genus Fenneralpheus Felder & Manning, 1986 for the country. These records bring to 11 the number of alpheid genera, and to four the number of species of Leptalpheus, known in Venezuelan marine waters.